2016
DOI: 10.1007/s00277-016-2703-1
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow niche in immune thrombocytopenia: a focus on megakaryopoiesis

Abstract: Immune thrombocytopenia (ITP) is an autoimmune disorder characterized by increased bleeding tendency and thrombocytopenia. In fact, the precise pathogenesis of this disease is still not clear. Megakaryopoiesis involves complete differentiation of megakaryocyte (MK) progenitors to functional platelets. This complex process occurs in specific bone marrow (BM) niches composed of several hematopoietic and non-hematopoietic cell types, soluble factors, and extracellular matrix proteins. These specialized microenvir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 74 publications
0
59
0
Order By: Relevance
“…It is known that there is a broad range of interactions between MSCs and their environment which means that the niche or microenvironment of these cells is vital for supporting and stimulating them to do their functions well (Khodadi et al 2016; Sobolewski et al 2005). Previous studies have shown the considerable effects of WJ-MSCs conditioned medium on up-regulation of several factors which assist in wound healing and increasing human skin fibroblasts expansion and migration in vivo (Arno et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that there is a broad range of interactions between MSCs and their environment which means that the niche or microenvironment of these cells is vital for supporting and stimulating them to do their functions well (Khodadi et al 2016; Sobolewski et al 2005). Previous studies have shown the considerable effects of WJ-MSCs conditioned medium on up-regulation of several factors which assist in wound healing and increasing human skin fibroblasts expansion and migration in vivo (Arno et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…1 ITP occurs either as a primary disorder or secondary to underlying neoplasia, infection, or autoimmune disease; in the latter case there may be more profound immune dysregulation. 2 The spleen plays a critical role in the pathogenesis of ITP ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…ITP involves isolated thrombocytopenia [4] as a result of anti-platelet antibody production by plasma cells that induce antibody-mediated platelet phagocytosis [5, 6], T-cell mediated platelet destruction [7], and/or impairment of megakaryocyte function [8-10]. In recent years, immune dysregulation due to ITP, especially cellular immune deficiency, has been an active area of research [11].…”
Section: Introductionmentioning
confidence: 99%